The status and influencing factors of death anxiety among Chinese college students under the COVID-19 pandemic: a cross-sectional study - Guangjian Li; Zhou Wang; Tingye Gao; Xin Gao; Junli Sun; Peng Li; Fengda Wu; Shouzhi Wu; Jie Zhou; Yaping Kong; Xugui Sun (BMC Public Health)
Abstract Background To comprehend the current state of death anxiety among Chinese college students during the COVID-19 pandemic, analyze its influencing factors, and provide recommendations for mitigating death anxiety among these students. Methods From March to May 2023, utilizing a cluster sampling method, students from three universities in Changzhou, Jiangsu, were selected as research participants. The investigation employed a general information questionnaire, the PTSD Checklist for DSM-5 (PCL-5), the Chinese Version Templer-Death Anxiety Scale (CT-DAS), and the brief version of the Big Five Inventory (BFI-10). Multivariate linear regression analysis was performed to examine the factors influencing death anxiety among Chinese college students during the COVID-19 pandemic. Results The total average score of death anxiety among the college students in this study was 44.35 ± 8.21. There was a positive correlation between death anxiety scores and both PTSD symptoms scores and neuroticism (r = 0.134, 0.255, both P < 0.01), and a negative correlation between death anxiety scores and extraversion, agreeableness, conscientiousness, and age (r=-0.135, -0.049, -0.172, -0.093, all P < 0.01). Multivariate linear regression analysis indicated that gender, age, place of origin, COVID-19 infection, PTSD symptoms scores, neuroticism, extraversion, and conscientiousness were significant factors influencing death anxiety among college students (all P < 0.05). Conclusions Death anxiety among Chinese college students during the COVID-19 pandemic is relatively high and is associated with gender, age, place of origin, COVID-19 infection, PTSD symptoms scores, and personality traits. Appropriate intervention strategies can be formulated based on these influencing factors.